Direct measurements of space-charge-regions in individual nanometer-scale crystals of Al2O3-rich magnesium-aluminate-spinel using off-axis electron holography and electron energy-loss spectroscopy. (15th September 2021) - Halabi, Mahdi; Kohn, Amit; Hayun, Shmuel
Abstract: Space charge regions (SCR) in ionic solids, a result of an uneven distribution of point defects, alter their thermodynamic, transport, mechanical, and optical properties. We examine the formation of SCR in nanometer-scale sized crystals of magnesium-aluminate-spinel with excess Al2 O3, MgO·1.27Al2 O3 . For this composition, the expected dominant point defects are anti-sites and cation vacancies. We determine the types, distribution and formation energies of charged point defects that form the SCR. Off-axis electron holography and electron energy-loss spectroscopy enabled to measure the electrostatic potential and distribution of Al · Mg anti-site charged point defects, respectively in individual crystals. We extract the width of the SCR, LSCR, between 1.7 and 2.1 nm. We measured the formation energy of charged vacancies following two extreme states, only aluminum or magnesium vacancies resulting in E f V ″ ′ A l = 1.09 ± 0.16 e V and E f V ″ M g = 1.04 ± 0.19 e V, respectively. For crystals considerably larger than LSCR, V ''' Al and VʺMg cation vacancies are the majority species at the particle core resulting in a negative charge density. When approaching the surface of the crystal, the space charge region is richer in Al · Mg defects. Finally, we examine the SCR as the crystal size is reduced, approaching LSCR . Measurements at particle cores of these crystals results in a positive charge due to the overlap of the SCR. Graphical abstract: Image, graphical abstract